Namṭ Takwîn al Bîah al Lughawiyyah fî Ma’had Dâr al Hijrah al Thalith li Taḥfîdh Al Qur’an Martapura - Oensyar, kamil Ramma; Mukhlis Anshari; Muhammad Syamsudin Noor (Uktub: Journal of Arabic Studies, 2023)
Conversational skills is one of the skills to be achieved in the teaching of modern languages including Arabic. Talking isthe primary means to build mutual understanding and mutual communication by using language as a medium. One of the factors that influence and determine the success of the learning process is the environment, not to mention the language environment. Quality language environment is something very important to the success of someone who is learning a second language, in this case Arabic. Bi’ah Arabiyyah is an environment where every activity is done with colored or Arabic. This method is very helpful in learning a foreign language because the students will apply and practice the language they have learned with no feeling nervous or embarrassed. Forming ability to speak Arabic and then enhance these capabilities is not easy, as the native language and the Arabic language has a lot of difference in terms of both linguistic and nonlinguistic. Training is needed to support the ability to speak Arabic. The exercises can be performed with the maximum if the language has created a conducive environment.